Modified blink dynamic index predicts activity and severity in patient with facial nerve palsy - Kim, Yuri; Lew, Helen (Frontiers in Ophthalmology, 2022)
Purpose: We analyzed the dynamics of blink and defined the blink index in facial nerve palsy(FNP) patients using ocular surface interferometer associated with clinical characteristics and clinical progress. Methods: In total, 49 patients were enrolled this study. All patients were tested using an ocular surface interferometer which used to measure blink patterns (total blink (TB), partial blink rate(PBR)) and blink dynamics (blink time (BT), lid closing time (LCT), closure time (CT), lid opening time (LOT), interblink time (IBT), closing speed (CS), and opening speed (OS)) using 600 frames recorded over 20 seconds. Distance of lagophthalmos and modified interpalpebral fissure(IPF), which was defined as the actual moving distance of the upper eyelid, subtracting the distance of lagophthalmos from the IPF, measured by Image J program. The types of FNP were “idiopathic”(Bell’s palsy) and “surgical”(following the neurosurgery). Patients classified into “acute” and “chronic” based on the duration of 6 months from the onset time of FNP. The clinical characteristics classified in to mild or severe according to the severe degree of exposure keratopathy, as "severe" if treatment such as tarsorrhapy and gold plate insertion was required. Results: Reduced MRD1, brow height, and modified IPF and increased lagophthalmos were noted in palsy side. LCT was longer and CS, modified CS and modified OS were shorter in palsy side. The LCT was longer and the modified CS was shorter in idiopathic patients with acute onset and with clinically severe. IBT was increased in idiopathic patients with clinically severe. Conclusion: With analyzing the blink patterns and blink dynamics, this study suggests a meaningful indicators among blink profiles and dynamics, LCT and modified CS based on modified IPF. It was more associated in the idiopathic type than in the surgical type of FNP patients. The modified CS can be a useful tool for evaluation the activity and severity indicator of FNP.